The effect of organizational culture and service quality on patient loyalty mediated by patient satisfaction - Fanggidae, Adhe William; Wahyoedi, Soegeng (Global Academy of Business Studies, 2025)
Purpose: This study examines the effect of organizational culture and service quality on patient loyalty, with patient satisfaction as a mediating variable. The research focuses on Siloam Kupang General Hospital, where improving service quality and cultivating a strong culture are essential for sustaining patient loyalty in a competitive healthcare environment. Methodology: A quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) was applied to data collected from 200 outpatients through structured questionnaires. Four latent variables organizational culture, service quality, patient satisfaction, and patient loyalty were analyzed using SmartPLS 4. Results: The findings reveal that both organizational culture (? = 0.293; p < 0.001) and service quality (? = 0.306; p = 0.001) significantly influence patient loyalty. Patient satisfaction also has a significant effect on loyalty (? = 0.294; p = 0.001) and mediates the relationships between organizational culture and loyalty (? = 0.141; p = 0.006), as well as between service quality and loyalty (? = 0.097; p = 0.034). The model demonstrates substantial explanatory power (R² = 0.633) and high predictive relevance (Q² = 0.462). Conclusion: Strengthening organizational culture and improving service quality are key strategies to enhance patient satisfaction and loyalty. Hospitals should prioritize patient-centered values, effective communication, and responsive services to build lasting trust. Limitations: The study is limited to a single hospital and a specific patient group, restricting generalizability. Contribution: This research extends the understanding of mediating mechanisms between culture, service quality, and loyalty, offering managerial insight for hospital service excellence and patient retention strategies.